Geomatica e Robotica: un connubio vincente verso l’automazione del rilievo - Eleonora Maset; Lorenzo Scalera (GEOmedia, 2022)
GEOMATICS AND ROBOTICS: A WINNING COMBINATION TOWARDS THE AUTOMATION OF THE SURVEY The discipline of Geomatics itself is experiencing a phase of profound innovation, resulting from an ever greater integration with technologies and methods developed, among others, in the field of Robotics and of IT.